(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Quinoline scaffolds have gained substantial interest in the modern era of medicinal chemistry due to their wide range of biological applications. The present work reported the synthesis of various oxime derivatives of quinolines by the reaction of substituted 2-chloro-3-formyl-quinolines with hydroxyl amine hydrochloride. The reaction was mediated by aqueous ethanol, whereas hexamine was used as an efficient, non-toxic and easily available basic organocatalyst. The developed protocol has various advantages, including operational ease, affordability, an eco-friendly approach, and short reaction time. Moreover, the synthesized compounds were subjected to in-vitro antimicrobial activities. The antimicrobial evaluation of almost all the compounds found to be potent and effective. Compounds 4c, 4d, and 4f showed a broad spectrum of inhibition and were more effective when tested against specific Gram (-) and Gram (+) bacteria. In in-vitro antifungal evaluation, all synthesized compounds (4a-4g) showed good sensitivity against the tested fungal cultures except Aspergillus niger.